Associations between cancer-related coping and depressive symptoms in oral cancer patients - ChunYing Cui; Lie Wang (BMC Psychology)
Abstract Objectives Specific coping styles have been found to influence several aspects of psychological health in various ways among cancer patients. Therefore, the aim of the current study was to examine whether different coping styles are associated with depressive symptoms in oral cancer patients. Methods The current cross-sectional study was conducted from May 2021 to October 2022 in Liaoning Province, China. A total of 229 patients were included. In addition to demographic and clinical information, the participants completed questionnaires on different coping styles and depressive symptoms. Multivariate linear regression was conducted to identify the influencing factors of depressive symptoms. Results The prevalence of depressive symptoms was 65.5% in oral cancer patients. Negative emotion and positive attitude coping explained an additional 50.1% of the variance in depressive symptoms. Negative emotion coping was significantly and positively associated with depressive symptoms (β = 0.596, p < 0.001), whereas positive attitude coping was significantly and negatively related to depressive symptoms (β=-0.275, p < 0.001). In addition, distant metastasis was associated with depressive symptoms (β = 0.084, p < 0.047). Conclusions In our sample, more than half of the oral cancer patients experienced depressive symptoms. Interventions based on decreasing negative coping and increasing positive coping should be implemented to help patients cope with mental health problems and achieve psychological adaptation after oral cancer diagnosis and treatment.